Ultra Fine Milling - Biooxidation Processing of Refractory Gold Concentrates - P. B. Marchant; J. T. Chapman; J. B. Austin; R. W. Lawrence (Canadian Institute of Mining, Metallurgy and Petroleum, 1990)
"Biohydrometallurgy is the use of microbiological reactions to assist in the extraction of metals. Bioleaching offers an innovative alternative for the treatment of refractory gold-bearing sulphides (1). One particular cost advantage of bioleaching is the potential to enhance gold extraction after only partial sulphide oxidation. The apparent selective sulphide oxidation is more prevalent where the refractory gold is associated with arsenic and antimony (2). Oxidation of the pyrite minerals and arsenopyrite at different oxidation rates can result in high gold extractions at relatively low levels of sulphide oxidation due to preferential, or selective, oxidation of the arsenic mineral. Arsenic extraction rates in a bioleach process typically exceed the iron extraction rate. Therefore, in concentrates in which the precious metals are principally associated with arsenic minerals, liberation of the precious metals may be possible with high recoveries and less than complete sulphide oxidation. The capital and operating cost advantages of partial sulphide oxidation are inherently obvious and are briefly illustrated herein.Ultra fine milling (UFM) is another alternative for enhancing gold extraction from refractory sulphides. Some refractory gold is simply particle size sensitive and UFM can improve gold extraction without the need for costly sulphide oxidation (3). Fine grinding technology for enhanced gold recovery developed by Metprotech, South Africa, is currently producing 2 - 4 micron ground product using a single pass, stirred ball mill. Proper application engineering has ensured that plug flow occurs through the mill. Plug flow from the feed inlet at the bottom of the reactor ensures that short circuiting of feed does not occur and as a result, the mill product does not require classification.A combination of UFM as a pretreatment for bioleaching could provide a mechanism for enhanced selective sulphide biooxidation and/or increased overall gold extraction following biooxidation due to improved particle liberation ( 4). The effect of UFM on biooxidation costs will be discussed. Only sulphide concentrates are considered herein for application of UFM in combination with biooxidation."